Soil moisture as a key factor in carbon release from thawing permafrost in a boreal forest - Song, Xiaoyan; Wang, Genxu; Ran, Fei; Huang, Kewei; Sun, Juying; Song, Chunlin (Geoderma, 2020)
The feedback between the atmosphere and permafrost soils containing large carbon stocks is currently considered the most important carbon-cycle feedback, but it is missing from climate models due to many uncertainties. Knowledge of how differences in post-thaw hydrological conditions affect carbon (C) release is critical for predicting permafrost feedback, but this knowledge remains limited. In this study, permafrost and active layer soils from the southern margin of the Eurasian boreal permafrost region in Northeast China were collected and incubated under experimentally modified moisture to monitor their CO2 and CH4 productions under simulated natural, drier and flooded conditions. We also characterized soil properties related to soil organic carbon (SOC) quality and microbial activities to determine their relations with measured C productions. We found that permafrost had higher C release per gram of SOC basis (C vulnerability) than the active layer, which suggested that there would be a high risk for C emissions in the permafrost region when permafrost thaws in the warming future. However, hydrological conditions following the permafrost thaw control these emissions. Permafrost C decomposed in relatively aerobic upland systems had higher C emissions than that decomposed in anaerobic wetland environments. Our results suggest a greater climate forcing of C release in aerobic than anaerobic conditions, but there are some uncertainties resulting from the unknown long-term CH4 production rates. Moreover, we found that the aerobic C production in permafrost after thawing could be constrained by water stress, suggesting that previous predictions based on soil incubations at natural soil moisture might overestimate the aerobic permafrost C release.